Obstacles of Using ICT in ELT in Secondary Schools of Bhojpur Municipality: A Quantitative Study - Rai, Uttam Sing (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
This study intended to investigate obstacles of using ICTs in ELT. Census method was adopted to obtain the objectives. Likert-scale survey questionnaire, non-participation observation and unstructured interview were adopted as the tools of data collection. The results of the study exhibits that majority of English teachers have been facing the obstacles such as insufficient infrastructure, expensive cost, lack of experts, unsteady of electric power and internet of using ICTs in ELT.